Presentation: Larsen's Human Embryology / Revised; 5th edition. – Churchill Livingstone, 2014. – 576 p. - Editorial office journal "Morphologia" (Морфологія, 2015)
Dear readers! In this edition of the magazine, the editorial board introduces the Larsen'sHumanEmbryology tutorial on embryology. The medical textbook includes a great artistic program, absolutely new online animations and high-quality images; clear descriptions and explanations of human embryonic development, based on modern scientific discoveries, keep you updated on the latest knowledge in this field.